Enhancing sustainable crop production through integrated nutrient management: a focus on vermicompost, bio-enriched rock phosphate, and inorganic fertilisers – a systematic review - Sande, Tamara José; Tindwa, Hamis J.; Alovisi, Alessandra Mayumi Tokura; Shitindi, Mawazo Jamson; Semoka, Johnson M. (Frontiers in Agronomy, 2024)
Securing a consistent food supply remains a pressing global challenge, particularly for small-scale farmers grappling with obstacles in enhancing agricultural yields, especially in tropical soils. Integrated Nutrient Management (INM) techniques, employing organic manures like vermicompost and bio-enriched rock phosphate, emerge as recommended solutions. Vermicompost is lauded for its nutrient richness and positive soil health impacts. At the same time, bio-enriched rock phosphate serves as a sustainable alternative to conventional phosphorus fertilisers, specifically tailored for tropical soil conditions. Despite individual studies assessing the effects of vermicompost, bio-enriched rock phosphate, and soluble fertilisers on plant growth, a comprehensive overview of their combined application is noticeably lacking. To fill this gap, this study employs the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) method to explore the synergies of combining these elements and their impacts on crop production and the environment. This review is among the first to comprehensively summarize the complexities of combining vermicompost, bio-enriched rock phosphate, and chemical fertilisers on various crops. It thoroughly examines potential advantages, disadvantages, effects on agricultural systems, socio-economic implications, and existing policies governing their usage. Our findings reveal that the combined application of vermicompost, bio-enriched rock phosphate, and soluble fertilisers leads to significant improvements in plant growth, yield, and soil properties. The optimal impact is observed when vermicompost constitutes 25% and soluble fertiliser comprises 75 or 100% of the recommended fertiliser dosage. Moreover, incorporating a mixture of phosphate-solubilizing bacteria (PSB) strains in rock phosphate further enhances its positive effects. Despite these positive findings, we identified gaps in comprehensive approaches addressing socio-cultural dimensions and the lack of literature on prevailing policies regarding vermicompost use in agricultural systems highlighting the need for a more holistic understanding of vermicompost incorporation and a better grasp of the institutional frameworks guiding these practices. However, to secure sustainable crop production, farmers need to integrate vermicompost and biofertilisers with chemical fertilisers. In fostering the adoption of sustainable and inclusive agricultural practices on small rural properties, it is advisable to incorporate agricultural education into farmer training programs.